Romulus and Remus, Two Phage Isolates Representing a Distinct Clade within the Twortlikevirus Genus, Display Suitable Properties for Phage Therapy Applications - Vandersteegen, Katrien (American Society for Microbiology, 2013)
The renewed interest in controlling Staphylococcus aureus infections using their natural enemies, bacteriophages, has led to the isolation of a limited number of virulent phages so far. These phages are all members of the Twortlikevirus, displaying little variance. We present two novel closely related (95.9% DNA homology) lytic myoviruses, Romulus and Remus, with double-stranded DNA (dsDNA) genomes of 131,333 bp and 134,643 bp, respectively. Despite their relatedness to Staphylococcus phages K, G1, ISP, and Twort and Listeria phages A511 and P100, Romulus and Remus can be proposed as isolates of a new species within the Twortlikevirus genus. A distinguishing feature for these phage genomes is the unique distribution of group I introns compared to that in other staphylococcal myoviruses. In addition, a hedgehog/intein domain was found within their DNA polymerase genes, and an insertion sequence-encoded transposase exhibits splicing behavior and produces a functional portal protein. From a phage therapy application perspective, Romulus and Remus infected approximately 70% of the tested S. aureus isolates and displayed promising lytic activity against these isolates. Furthermore, both phages showed a rapid initial adsorption and demonstrated biofilm-degrading capacity in a proof-of-concept experiment.